0398 Improvement in Sleep Duration and Maintenance with Ion Powered Continuous Release and Absorption Melatonin in a Cohort of Patients with Chronic Short Sleep Duration: Results from a Patient-Reported Outcomes Study. (12th April 2019) - Seiden, David J; Brodner, David C; Shah, Syed M
Abstract: Introduction: Numerous epidemiologic studies have demonstrated that short sleep duration has negative health consequences. Chronic sleep loss places a direct and indirect societal cost burden of more than $90 billion annually. Patients sleeping ≤ 4-5 hours should be regarded as high risk for all-cause mortality. Continuous Release and Absorption Melatonin (CRA-melatonin) with its Ion Powered Pump (IPP) delivery technology was hypothesized to provide the desired 7-hour pharmacokinetic (PK) profile for this population. Methods: Patients who received a sample of CRA-melatonin (Remfresh) from their physicians were invited to complete a 13-question online survey. Questions included average hours of sleep before and after taking CRA-melatonin and number of middle of the night awakenings, as well as improvement in sleep onset, maintenance, and quality. Results: 175 patients who self reported sleeping ≤ 4 h per night were analyzed. Prior to taking CRA-melatonin, over 90% of these patients indicated they suffered sleep disturbances nightly. After taking CRA-melatonin, the percentage of patients achieving an improvement in sleep duration was 96.6%, including more than half (52.0%) achieving a sleep duration of ≥ 6 h. 95.7% reported a major/moderate improvement in sleep maintenance. 99% reported a major/moderate improvement in sleep quality. This study is ongoing. Conclusion: With CRA-melatonin and its 7-hour PK profile, the majority of patients (96.6%) previously experiencing chronic, short sleep duration of ≤ 4 h achieved an improvement in sleep duration, including (52.0%) who achieved a sleep duration of ≥ 6 h. The results provide real-world evidence that CRA-melatonin with its extended 7-hour PK plateau time may be a practical baseline therapy to improve sleep duration and other key sleep parameters in these high-risk patients for all-cause mortality. Support (If Any): This study was supported by Physician's Seal LLC.